Livestock Waste Management in Kenya: A Futuristic Perspective - Rachuonyo , H. A.; Kitilit , J. K.; Mabonga , G. N.; Mukhwana , E. J.; Kios , D. K.; Ongubo , M. N.; Oliech , G. O. (African Journal of Education,Science and Technology (AJEST), 2025)
Livestock waste management remains a major global concern because of nitrogen and phosphorus pollution, environmental safety and quality of crop and animal products. Livestock production is the largest source of atmospheric ammonia, accounting for over 40 % of the global inventory. Sources of wastes are production farms and slaughter/processing/packing plants. Objective of livestock waste management is to make best use of nutrients in manure while protecting natural resources from pollution for improved environmental quality and sustainability. When managed properly, manure can be a valuable resource for farmers especially in rural areas; providing nutrients for crops, generating income, improving nutrient use efficiency, among other benefits. However, if la nd is insufficient to use generated manure or if mismanaged, then pollution risks to water supplies and other ecosystem resources could result. Unmanaged waste could be breeding grounds for disease causing pathogens and vectors, generate odour, ruin aesthetic values, increase production costs and reduce farm product quality, among other dangers. Best management practices to reduce negative impacts include feed manipulation & feeding strategies, breeding for improved feed intake, as well as diligent management and use of improved technologies on handling, processing and disposal. Three main forms of manure are solid, liquid and slurry, each of which has its way of handling, management and disposal. Options for managing waste include composting, processing for sale, aerobic & anaerobic lagoon treatment, vegetative waterways, soakaway ponds, biogas production or direct land application. All these methods are practised with varying degrees of success in Kenya. Considering rapid population increase and subsequ ent land fragmentation, many farmers are constrained when it comes to available options. Determinant factors on choice include financial constraints, production systems in place, size of farm operations, compliance with local and international laws/regulations and standards, land availability, awareness of existing technologies, among others. This paper review and shares best practices and global trends for manure management in general, with Kenya‟s future in mind, to ensure improved environmental quality and economical usage. This will have both short and long term economic and environmental impact that benefits production system in the country and beyond.